The Value Preferences of the Parents in Turkey towards Their Children - Zafer Kuş (Journal of Social Science Education, 2014)
The current study aims to determine the values parents in Turkey try to teach their children. Parents from various cities (Ankara, Diyarbakır, Hakkâri, Hatay, Iğdır, İstanbul, Kastamonu, Kırşehir, Muğla) around Turkey were selected through maximum variation sampling, a purposive sampling method. The current study was conducted within the qualitative research methods. Results were obtained through content and descriptive analyses of data collected with open-ended question forms. Parents try to teach the value of honesty as the first priority within family. Other values that families try to teach their children are, respectively, giving importance to family unity, respect, responsibility, affection, industriousness, patriotism, care for health, and tolerance.